Violencia intrafamiliar y dependencia emocional en una joven de 19 años de la Parroquia Zapotal - Acosta Quiñónez, Deyaneira Elizabeth (2023)
Domestic violence is a way of violating the rights against the integrity, health, and well-being of women, be it of a physical, sexual or psychological nature. Intrafamily violence in its modality of partner violence produces mainly psychological consequences in battered women such as emotional disorders of depression and anxiety, low self-esteem, sleep disturbances, difficulties to maintain concentration and in some cases advanced stress. However, recent research has associated domestic violence with emotional dependence. The objective of the work is to determine how intrafamily violence has affected the emotional dependence of a 19-year-old girl from the Zapata parish, using for this purpose the semi-structured interview, clinical history, direct observation, Beck's depression inventory., the Hamilton anxiety scale, the Davidson trauma scale, and an open-ended questionnaire. The results of the psychological instruments reveal that the patient presents features of moderate anxiety as well as somatic and psychic symptoms of moderate anxiety, the stress caused by the traumatic environment of violence is below the range, plus what was manifested by the young woman in the open question questionnaire; place the patient in a diagnostic criterion of moderate emotional dependence. Jointly interpreting the findings of the psychological tests and what was reported by the patient in her speech; It is established that the violence that he has suffered at the hands of his partner for approximately a year has interfered significantly in his problem of emotional dependency.